Influence of narcissism CEO, islamic background CEO, and educational background CEO on company financial performance : EMPIRICAL STUDY ON COMPANIES REGISTERED ON JII 70 IN 2020-2023 - Afifah, Nurul; Arinta, Yusvita; Firdaus, Nadia Nurul (Islamic Accounting Journal, 2024)
Abstract Objective & object: The aim of this study is to find out whether CEO narcissism, CEO Islamic background, and CEO educational background can affect the financial performance of companies listed in the JII 70 years 2020–2023. Methods: The approach used by the author in this study, the quantitative research approach, is an objective research method that includes data collection and analysis through the use of statistical testing techniques. The location of this research was companies listed in the Jakarta Islamic Index 70 (JII 70) in various industrial sectors from 2020 to 2023. The research was conducted in December 2023. The author used purposive sampling techniques and obtained 38 company samples. Results & Conclusions: According to the statistical tests carried out by the author, CEO Narcissism has a positive and significant influence on the financial performance of the company, while CEO Islamic Background has no effect on the company's financial performance. Furthermore, earnings management cannot moderate the relationship between CEO narcissism and the company's financial performances, while earning management can moderate CEO's relationship with the company. Limitations: In conducting this research, there is newly published research data so that the time for collecting and processing data is limited. Implications: The impact of being a CEO: Narcissism has a positive and significant impact on the financial performance of the company and attracts potential investors to invest in the company because the high or low confidence of the CEO will have an impact on financial performance. Keywords: Narcissism CEO; Financial Performance; Earnings Management. Abstrak Tujuan & obyek: Tujuan dari penelitian ini adalah untuk mengetahui apakah CEO narcissism, CEO islamic background, dan CEO educational background mampu mempengaruhi kinerja keuangan perusahaan yang terdaftar di JII 70 tahun 2020-2023. Metode: Metode pendekatan yang digunakan penulis dalam penelitian ini dengan pendekatan Penelitian kuantitatif adalah metode penelitian objektif yang mencakup pengumpulan data dan analisisnya melalui penggunaan teknik pengujian statistic. Lokasi penelitian ini dilakukan di perusahaan yang terdaftar di Jakarta Islamic Indeks 70 (JII 70) dalam sektor aneka industri dari tahun 2020 hingga 2023. Penelitian dilaksanakan pada bulan Desember 2023. Penulis menggunakan teknik purposive sampling dan memperoleh 38 sample perusahaan. Hasil & Simpulan : Dari hasil uji statistik yang dilakukan oleh penulis didapatkan bahwa CEO Narcissism berpengaruh positif dan signifikan terhadap kinerja keuangan Perusahaan sementara CEO Islamic Background tidak berpengaruh terhadap kinerja keuangan Perusahaan. Selanjutnya Earnings management tidak dapat memoderasi hubungan CEO narcissism terhadap kinerja keuangan Perusahaan sedangkan Earnings management dapat memoderasi hubungan CEO Islamic Background terhadap kinerja keuangan Perusahaan. Untuk Earnings management tidak dapat memoderasi hubungan CEO Educational Background terhadap kinerja keuangan perusahaan. Keterbatasan: Dalam melakukan penelitian ini terdapat data data penelitian yang baru diterbitkan sehingga waktu pengumpulan dan pengolahan data menjadi sempit. Implikasi: Dampak dari adanya CEO Narcissism berpengaruh positif dan signifikan terhadap kinerja keuangan Perusahaan untuk menarik calon investor untuk berinvestasi di perusahaan tersebut karena tinggi atau rendahnya kepercayaan diri dari CEO akan berdampak pada kinerja keuangan.